A Study of Customer Satisfaction with Oversea Online Shopping for Overseas Chinese People - Chunhua, Chen (International Journal of Multidisciplinary in Management and Tourism, 2020)
in Southeast Asia countries, many Chinese people also willing to oversea shopping online , but they found difficult in forwarding service with oversea online shopping , lead to consumer satisfaction levels drop . With the increasing income and busy working, many people would like to shop online. Moreover, the most reasons for oversea Chinese like to shopping online in China are cheaper products and familiar Chinese products that are used to use in China. Online shopping , for customer it is not only because of the high level of convenience , but also because of the broader selection ; competitive pricing and greater access to information . But oversea Chinese found difficulties in forwarding service and payment service for online shopping in China . So online shopping for oversea people ‘s satisfaction with the overall decline . In begin of 2014, company Alibaba pushed out a new program named ‘Sea.taobao.com. This new program support with international forwarding service and payment by Visa , Master card & JCB for Southeast Asia countries’ consumers .The company wants to know that how customers feel towards it , then improve this program to increase sales . So this research study is focusing on ‘Sea. taobao.’ & consumer’s feeling after taking part in online shopping on Sea.taobao.com. Many consumers still worried about the security of shopping and long lead time & expend forwarder feeds. Due to forwarder fees for shopping on Sea.taobao.com still expensive than shopping in Taobao.com , which is the website for within China . Company Alibaba shall cooperation with forwarder in Southeast Asia countries, which can delivery goods in short time along with cheaper forwarding fees. About security, the company shall cooperation with the bank Southeast Asia countries to increase consumer reliance.